2012
DOI: 10.1260/0958-305x.23.2-3.283
|View full text |Cite
|
Sign up to set email alerts
|

CCS in the Media: An Analysis of International Coverage

Abstract: Internationally, the level of public awareness of carbon dioxide capture and storage (CCS) technology remains low. The mainstream media have a salient influence in shaping the debate on CCS's implementation and its risks. This paper presents the results of analysis of print media coverage of CCS worldwide between August 2009 and June 2010. A total of 1138 articles from the Carbon Sequestration Leadership Forum were reviewed and analysed. The majority of these articles were balanced or neutral in tone and lacki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Several studies have referred to some sort of agenda‐setting or framing in analyzing media attention to CCS (e.g., Ashworth & Quezada, ; Boyd & Paveglio, ; Dowd et al, ; Mander & Gough, ; Nerlich & Jaspal, ). The most common positive and negative frames are an example of analysis of social construction of CCS in media (Boyd & Paveglio, , pp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have referred to some sort of agenda‐setting or framing in analyzing media attention to CCS (e.g., Ashworth & Quezada, ; Boyd & Paveglio, ; Dowd et al, ; Mander & Gough, ; Nerlich & Jaspal, ). The most common positive and negative frames are an example of analysis of social construction of CCS in media (Boyd & Paveglio, , pp.…”
Section: Methodsmentioning
confidence: 99%
“…The role of media is especially interesting in debates on controversial emerging technologies such as carbon capture and storage (CCS). Studies have more often focused on how media has framed and represented CCS in country‐specific data (Boyd & Paveglio, ; Nerlich & Jaspal, ; van Alphen, van Voorst tot Voorst, Hekkert, & Smits, ), but a comparative approach has also been applied (Buhr & Hansson, ; Dowd, Ashworth, Rodriguez, & Jeanneret, ). This technology, which is claimed to be one potential means of climate change mitigation, is operational in 12 large‐scale projects around the world (GCCSI, ), but deployment has not advanced as quickly as anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous media analyses of fossil fuel based CCS projects [51,[115][116][117] have shown the majority of media coverage to be balanced or neutral in tone, lacking in technical detail, with a focus on reporting the progress of pilot and demonstration projects and funding issues. A link has been made between a general journalistic lack of understanding of the CCS technology itself and the number of questions and concerns raised [116].…”
Section: The Role Of the Mediamentioning
confidence: 99%
“…A link has been made between a general journalistic lack of understanding of the CCS technology itself and the number of questions and concerns raised [116]. This has led to journalists producing articles that are speculative in nature as to what CCS can actually achieve as opposed to providing factual and accurate descriptions of the technology's capability.…”
Section: The Role Of the Mediamentioning
confidence: 99%
“…One can argue that the media might have an influence on public opinion development, or at least that what is in the media reflects what is in the public opinion. Dowd et al (2012) argue that mass media is understood to play a key role in generating public concern about particular issues and uncertainties associated with such new technologies. van Alphen et al (2007) found an increase in the amount of articles about CCS in the Dutch written media up to 2007; following this Kliest (2010) states that this increase as well as the increase they find in later years reflects the development of public opinion.…”
Section: Introductionmentioning
confidence: 99%